Study on Crystallization Behaviour of Polypropylene Containing Nano-Calcium Carbonate and Organic Nucleating Agents - GUANGMEI, CHEN; YE, CHEN; YIPING, HUANG (Asian Journal of Chemistry, 2010)
The crystallization behaviour of polypropylene (PP) and PP with additives was investigated by DSC. It was found that the crystallization temperatures and the crystallization rates of PP increased with the addition of nanometer-scale calcium carbonate (nm CaCO3) and with the increasing amount of the organic nucleating agents 1,3; 2,4-di-p-chlorobenzylidene sorbitol (CDBS). The crystallization temperature for the PP with CDBS was higher than for non-nucleated PP by 20-25 K when the samples were cooled from molten. The values of Avrami exponent ‘n’ indicated the addition of nm CaCO3 and CDBS could affect the nucleation process and the crystalline morphology. Three methods are used to deal with the non-isothermal crystallization process for PP and nucleated PP. Ozawa equation could not describe satisfactorily the nonisothermal crystallization behaviour of PP with CDBS in this study, while Mo's method could. The results obtained by modified Avrami equation indicate that the primary crystallization stage for nonisothermal melt crystallization might correspond to a threedimensional spherical growth with thermal nucleation. The nonisothermal crystallization kinetic parameters revealed that the addition of nm CaCO3 and CDBS increases the crystallization rate of PP from the molten state obviously. The results of DSC and the polarized light microscopy display CDBS is an effective nucleating agent for PP. But more CDBS in samples may affect the crystalline morphology of PP.